2017
DOI: 10.1016/j.eururo.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Biomarkers of a Randomized Trial Comparing First-line Everolimus and Sunitinib in Patients with Metastatic Renal Cell Carcinoma

Abstract: Background Metastatic renal cell carcinoma (RCC) patients are commonly treated with vascular endothelial growth factor (VEGF) inhibitors or mammalian target of rapamycin inhibitors. Correlations between somatic mutations and first-line targeted therapy outcomes have not been reported on a randomized trial. Objective To evaluate the relationship between tumor mutations and treatment outcomes in RECORD-3, a randomized trial comparing first-line everolimus (mTOR inhibitor) followed by sunitinib (VEGF inhibitor)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
163
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 183 publications
(180 citation statements)
references
References 31 publications
6
163
3
3
Order By: Relevance
“…One possible reason for a survival advantage in patients with KDM5C mutations may be an improved response to VEGF inhibitor therapy. We have recently published data showing prolonged progression-free survival among these patients (20.6 months for patients with KDM5C mutations vs 8.3 months for KDM5C wild-type),[21] and other recent research has yielded similar results [22]. In regard to SETD2 mutations, previous studies have indicated these mutations are associated with advanced or recurrent disease.…”
Section: Discussionmentioning
confidence: 64%
“…One possible reason for a survival advantage in patients with KDM5C mutations may be an improved response to VEGF inhibitor therapy. We have recently published data showing prolonged progression-free survival among these patients (20.6 months for patients with KDM5C mutations vs 8.3 months for KDM5C wild-type),[21] and other recent research has yielded similar results [22]. In regard to SETD2 mutations, previous studies have indicated these mutations are associated with advanced or recurrent disease.…”
Section: Discussionmentioning
confidence: 64%
“…However, a wide range of clinical outcomes has been observed. Interestingly, genomic study of RECORD-3, a large clinical trial randomized kidney cancer patients to either VEGFR or mTORC1 inhibitors, demonstrated that ccRCC with mutant PBRM1 associates with longer progression free survival (PFS) on everolimus, an mTORC1 inhibitor, at 12.8 months than those with wild-type PBRM1 at 5.5 months (Hsieh et al, 2015; Hsieh et al, 2016). In parallel, the Vhl F/F Pbrm1 F/F Ksp-Cre ccRCC and human VHL and PBRM1 mutated ccRCC shared mTORC1 pathway aberration.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, these genes encode chromatin and epigenetic regulatory proteins, and most mutations are predicted to result in functional loss, favoring their roles as tumor suppressors (Hakimi et al, 2013b). PBRM1 , the second most commonly mutated gene in all stages of ccRCC (Hsieh et al, 2016), encodes BRG1-associated factor (BAF) 180, the defining subunit of the ~2 MDa Polybromo BAF (PBAF) SWI/SNF complex (Varela et al, 2011). The SWI/SNF chromatin remodeling complexes are macromolecular machineries, which utilizes ATP to mobilize nucleosome and thereby modulate chromatin structure (Biegel et al, 2014; Clapier and Cairns, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, owing to the predominance of clear cell histology in metastatic disease (83–88%) 12,13 , tumours with non-clear cell histology have been grouped as ‘nccRCC’ (Table 1) for feasibility in conducting clinical trials 1416 . Furthermore, recent cancer genomic studies have revealed an overt complexity of intra-tumour 1719 and inter-tumour 7,20 heterogeneity in ccRCC, which could contribute to the heterogeneous clinical outcomes observed 2123 .…”
Section: Introductionmentioning
confidence: 99%